Quality of life and associated factors among the youth with substance use in Northwest Ethiopia: Using structural equation modeling. - Gebrekidan Ewnetu Tarekegn; Goshu Nenko; Sewbesew Yitayih Tilahun; Tilahun Kassew; Demeke Demilew; Mohammed Oumer; Kassahun Alemu; Yassin Mohammed Yesuf; Berhanie Getnet; Mamaru Melkam; Eden Abetu Mehari; Biruk Fanta Alemayehu (PLoS ONE, 2022)
Background Substance use leads to serious clinical conditions with the potential to cause major health and emotional impairments in individuals. Individuals with substance use typically report significantly poorer QoL than the general population and as low as those with other serious psychiatric disorders. It has a high impact on morbidity, mortality, and productivity, it also compromises the general safety and performance of the users, i.e., affects the quality of life. Therefore, this study aimed to assess quality of life and identify the potential predictors among youths who use substances. Methods A multicenter cross-sectional study design was applied to assess quality of life and associated factors among substance use youths in the central Gondar zone from January 1 to March 30/ 2021. A total of 373 substance use youths were included in the study. The data were collected using face-to-face interview by structured questionnaires, and entered to Epi-data version 4.6 and exported to STATA version 16, and AMOS software for further statistical analysis. To identify factors associated with health-related quality of life, structural equation modeling was used, and it also used to estimate the relationships among exogenous, mediating, and endogenous variables. Results Substance used youths had a moderate overall health-related quality of life (mean score = 50.21 and 14.32 standard deviation, p-value < 0.,0001), and poor health-related quality of life in the environmental health domain (mean score of 45.76 with standard deviation of 17.60). Age (β = 0.06, p<0.001), sex (β = 0.30, p<0.001), psychotic symptoms (β = -0.12, p<0.001), employment status (β = 0.06, p = 0.008,), loss of family (β = 0.35, p<0.001), and social support (β = 0.27, p<0.001) were variables significantly associated with health-related quality of life. Conclusion According to the findings of this study, substance abuse during adolescence is associated with lower health-related quality of life and a higher report of psychopathological symptoms. Given this finding, mental health and health promotion professionals should learn about and emphasize the impact of substance use on youth quality of life.